Transformation of Spirituality in Contemporary Muslim Life - Hayati, Hayati; Kadir, Abdul; Putri, Wahyuni Eka; Novanto, Riza Awal; Muslimin, Muslimin (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
This paper describes the transformation of spirituality in contemporary Muslim life. The transformation of spirituality in contemporary Muslim life involves changes in the understanding and practice of spirituality in modern Muslim society. The purpose of this study is to find out and understand how the transformation of spirituality in contemporary Muslim life occurs. The method used in this study is an exploratory qualitative research method that attempts to analyze research problems from reading sources by applying content analysis. Researchers use qualitative research to review the results of previous studies and to interpret a phenomenon scientifically. Data collection techniques are carried out through documentation techniques from various journals, proceedings, online news, and relevant books. The results of this study explain how the transformation of spirituality in contemporary Muslim life occurs and to deepen the understanding and practice of spirituality in Islam, seeking a balance between the world and the hereafter. The conclusion of this study is that understanding the transformation of spirituality in contemporary Muslim life will be able to develop good relationships between humans and their God and between humans and other humans. The limitation of this study is the lack of data availability to analyze the transformation of spirituality in contemporary Muslim life. The researcher’s hope for future researchers is that they will be able to develop further the spiritual transformation of contemporary Muslim life.